Optimizing Organ Donation After Euthanasia: A Critical Appraisal - E. A. J. Alkemade; H. D. Lam; B. J. C. Hendriks; A. E. Braat; I. P. J. Alwayn; M. J. Coenraad; A. G. Baranski (Transplantology)
This Critical Appraisal aims to explore the pharmacokinetics and pharmacodynamics of medications used in organ donors after euthanasia (ODE) and their impact on abdominal organ quality. With the legalization of ODE, the donor pool has expanded, but it has introduced complexities regarding organ quality. This study evaluates existing euthanasia protocols in the Netherlands, Belgium, Spain, and Canada, focusing on differences in the medication types and dosages. Additionally, a literature review assessed the potential hepatotoxic effects of high-dose medications like thiopental, propofol, and non-depolarizing neuromuscular blocking agents. High doses of non-depolarizing neuromuscular blocking agents, particularly rocuronium, are associated with hepatotoxic effects in vitro. Furthermore, thiopental doses exceeding 750 mg significantly increase the risk of liver dysfunction. Recent findings also indicate that high-dose propofol and lidocaine can slightly prolong the time to death, which is crucial for optimizing organ viability in ODE. This study highlights the need to optimize organ donation procedures after euthanasia. Further research is needed to achieve this balance, maintaining the integrity and ethical standards of the euthanasia process while enhancing the outcomes of organ donation.